Analisa Pengaruh Corporate Governance, Ownership Structure, dan Cash on Hand Terhadap Nilai Perusahaan - Agus Arianto Toly; Cindy Claudya; Rezky Santoso; Felicia Grace (Program Studi Akuntansi, Universitas Kuningan, 2020)
The purpose of this study was to investigate the effects of corporate governance, ownership structure, and cash on hand on Firm Value on manufacturing companies listed in Indonesia Stock Exchange. The dependent used in this study was the firm value whereas the independent used in this study were the corporate governance, ownership structure, and cash on hand. This study used these following measurement methods: Tobin’s Q - used to measure the firm value; board size, independent director, and audit quality were used to measure the corporate governance, proportion of managerial ownership was used to measure the ownership structure, and natural logarithm of year-end cash was used to measure the cash on hand. This study also used the leverage, firm size, firm age, and dividend payment as controlling variables. The sample of this study consisted of 74 manufacturing firms obtained from Indonesia Stock Exchange from year 2014 to 2017. The technique used for this analysis was the multiple regression. The result of this study suggested that the cash on hand had negative and significant effects on firm value when the leverage, firm size, firm age, and dividend payment were used as controlling variables. On the other hand, this study also suggested that the corporate governance and managerial ownership had no significant effect on the firm value when the leverage, firm size, firm age, and dividend payment were used as controlling variables. Keywords: firm value, corporate governance, ownership structure, cash on hand